Diabetes mellitus is associated with elevated urinary pyrrole markers of γ-diketones known to cause axonal neuropathy. Issue 1 (10th September 2020) - Chen, Xiao; Liu, Wei; Wang, Lu; Lin, Dafeng; Nie, Lulin; He, Kaiwu; Guo, Zhiwei; Zhu, Feiqi; Feng, Wenting; Liu, Weimin; Yuan, Jing; Yang, Xifei; et al.
Abstract : Introduction: Progressive distal symmetrical axonal neuropathy, a complication of diabetes mellitus (DM), has an unknown cause. Normal physiological metabolism and diabetic dysmetabolism are associated with the generation of γ-diketones. γ-Diketones form pyrroles with protein amines, notably with axonal proteins required for the maintenance of nerve fiber integrity, especially elongate, large-diameter peripheral nerve fibers innervating the extremities. We tested the hypothesis that neuropathy-associated γ-diketone pyrroles are elevated in DM. Research design and methods: We measured the urinary concentration of γ-diketone pyrroles in age-matched and gender-matched elderly (60–84 years) persons with (n=267) or without (n=267) indicators of DM based in a community population (9411 community older adults aged ≥60 years) in Shenzhen city, Guangdong, China. We used statistical methods, including a generalized linear model, multivariate logistic regression analysis and restricted cubic splines, to assess linear and nonlinear relationships between urinary γ-diketone pyrroles and indicators of DM. Results: Compared with healthy controls, those with DM had significantly higher levels of fasting blood glucose, glycated hemoglobin A1c, urinary ketone bodies and urinary γ-diketone pyrroles. The median concentration of urinary γ-diketone pyrrole adducts was significantly higher (p<0.0001) in individuals with DM (7.5 (5.4) μM) compared with healthy controls (5.9 (4.3) μM). Both linear and non-linear relations were found between urinary γ-diketone pyrroles and indicators of DM. Conclusions: Diabetic dysmetabolism includes increased generation and excretion of neuropathy-associated γ-diketone pyrroles. These findings form the foundation for studies to test whether γ-diketone pyrrole concentration correlates with quantitative sensory (vibration and temperature) and electrodiagnostic testing.